UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MEMPERBAIKI SISTEM STARTER MELALUI METODE DEMONSTRASI PADA SISWA KELAS XII TKR SMK N 1 GABUSWETAN INDRAMAYU TAHUN AJARAN 2013/2014 - Dwi Nurviyanto; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this study was to determine the increase in student motivation and student learning outcomes by applying the learning method demonstration on learning fix a starter system in SMK N 1 Gabuswetan Indramayu academic year 2013/2014. The main focus of this study is the difference in student motivation and student learning outcomes of students before and after implementing the learning demonstration method in a class. This research is classroom action research. The subjects in this study were students of class XII TKR B SMK N 1 Gabuswetan Indramayu academic year 2013/2014, amounting to 35 students. Objects in this study is based on an increase in motivation and learning outcomes through the demonstration method of fixing the starter system. The research was conducted in three cycles with four stages of classroom action research, namely: planning, implementation, observation, and reflection on each cycle. Data collection techniques obtained through the use of multiple choice questions (pre-test and post-test), observation of student activity sheets and motivation questionnaire (before and after the demonstration methods implemented). The analysis used is the analysis of quantitative data with descriptive statistics. Results of research show that after the implemented demonstration method of motivation and learning outcomes showed improvement. Learning motivation increased from 49% pre-cycle (less motivated category) to 74.6% (medium motivation category). Learning outcomes produce an average yield of pretest and post-test on the first cycle is 37 to 70.71 of 35 students, the average value of the class on the second cycle of the pre-test value of 40.29 into a post-test value 66.85 and the third cycle value average class in the third cycle is increased from pre-test value of 38.65 and post-test value to 76. After all the activities that students end up achieving completeness criteria or achieve ≥ 75 there were 28 students or 80% of the total number of students (80%> 60% = pass in classical).